Mossbauer spectroscopy : principles and applications - Maddock, A. G. (Alfred Gavin) (Horwood chemical science series., 1997)
Mossbauer spectroscopy has proved itself a versatile technique, finding applications in diverse areas of science and industry. Starting from physics and chemistry it spread into biochemistry, mineralogy, biochemistry, corrosion science, geochemistry and archaeology, with applications in industrial and scientific research. The author aims to help advanced university students, professionals and research workers who ask the question "what's in it for us?". After a concise account of experimental techniques, he emphasizes those applications in which there are few, if any, alternative ways of obtaining the same information about electron fields and the nuclei. He explains areas of industrial interest, including the important applications related to tin and iron on which there is much activity in research and development, and interprets the extension of Mossbauer techniques to main group, transitional and other suitable elements. Attention is paid to factors which may lead to misinterpretation of spectra and another chapter covers the complexities of interpreting emission spectra. Discusses the appearance of Mossbauer spectroscopy in biochemistry, mineralogy, biochemistry, corrosion science, geochemistry and archaeology, with applications in industrial and scientific researchEmphasizes the applications in which there are few, if any, alternative ways of obtaining the same information about electron fields and the nucleiAttention is paid to the complexities of interpreting emission spectra and the factors which may lead to misinterpretation of spectra.